Nutritional Status of Patients on Maintenance Hemodialysis as Assessed by Mini Nutritional Assessment Survey- Short Form and Anthropometric Measurements. - Rizvi, Nabiha; Baig, Moeena (Pakistan Journal of Kidney Diseases, 2021)
Protein calorie malnutrition is common in chronic kidney disease patients especially on maintenance hemodialysis (MHD). Multiple factors including mainly frequency and adequacy of dialysis and dietary habits may result in malnutrition besides other comorbidities. Different tools have been designed to analyze the nutritional status of dialysis patients including subjective global assessment, malnutrition inflammation score, Mini Nutritional Assessment– Short Form (MNA-SF) and several others. We assessed the nutritional status of our MHD patients using Mini Nutritional Assessment–Short Form (MNASF) Methods Total of 44 patients aged between 13 to 64 years, undergoing MHD for at least 6 months were included in the study. Results Out of 44 patients 63% patients were malnourished, 34% were at risk of malnutrition and 3% were having normal nutritional status according to MNA-SF. The mean of mid-arm circumference was low even in the presence of mean albumin and BMI within the normal range. Conclusion Nutrition is a neglected aspect of the dialysis patients. Multiple factors including poor socioeconomic status, lack of knowledge and poor dietary compliance lead to significant malnutrition among MHD patients.